Answer:
See below, sorry for taking so long
Explanation:
1.
A. Slope is rise over run or y2 - y1 divided by x2 - x1
We have (-5, 1) and (-3, 7)
7 - 1 / -3 - (-5)
6 / -3 + 5
6 / 2 = 3
Slope = 3
B. So point slope form is y - y1 = m(x - x1)
We know the slope so:
y - 1 = 3(x - (-5))
C. Using the point slope we can move things around to get slope-intercept:
y - 1 = 3(x + 5)
y - 1 = 3x + 15
y - 1 + 1 = 3x + 15 + 1
y = 3x + 16
D. Standard form is Ax + By = C:
y = 3x + 16
y - y = 3x + 16 - y
0 = 3x + 16 - y
0 - 16 = 3x + 16 - y - 16
-16 = 3x - y
3x - y = -16